El cuento fantástico como herramienta didáctica para el fortalecimiento de la oralidad en estudiantes de tercer grado de primaria en una institución pública de Bogotá (2016)
This project aims to strengthen orality in third grade students of a public institution in Bogotá, through the fantastic tale and the use of some oral communication techniques such as the round table and the debate. According to the results of a Language diagnostic test, in which students showed difficulties at exposing and arguing, a didactic unit is proposed based on the stories of Pumi, "The elf carpenter ´elf ”, written by Ellis Kaut.